PENGARUH LANDRENTE TERHADAP PENGUASAAN TANAHA DAN PENGGUNAAN TANAH DI KECAMATAN MANGUHARJO MADIUN 1860-1870 - Nurtanti, Ike Evi (Candi, 2014)
The objective of research was to find out: (1) the background of landrente implementation and the implementation of landrente in East Indies by Raffless in 1811-1816, (2) the implementation of landrente in Madiun in 1811-1816, (3) the effect of landrente on land mastery in Mangunharjo Subdistrict of Madiun in 1860-1870, (4) the effect of landrente on land use in Mangunharjo Subdistrict, Madiun in 1860-1870.This study employed a historical research form, an undertaking to study and to explore the facts and to drawn a conclusion concerning the past events. In this research, source analysis technique was used with historical research method. The source employed included primary sources encompassing archive and document in the period of landrente enactment, and secondary sources encompassing books, article, and interview related to landrente particularly in Madiun.Considering the result of research, it could be concluded that: (1) land rent (landrente) system in Madiun had started to be enacted during Raffles reign in 1811-1816 in, among others, Mangungharjo Subdistrict, Madiun City, (2) the application of landrente affected the land mastery and land use by the society, (3) the society land mastery changed from individual land ownership into communally land ownership (land communalization) pattern, while the society land used changed from agricultural purpose with rice as main commodity into sugarcane land opening. Keywords: landrente, landrente in Madiun.